The Effects of Secondary Special Education Preparation in Reading: Research to Inform State Policy in a New Era. (February 2018) - Knackstedt, Kimberly M.; Leko, Melinda M.; Siuty, Molly Baustien
In this study, the authors present findings from a survey of 577 secondary special educators in a large Midwestern state regarding their reading pre-service and in-service teacher preparation and its effect on teachers' sense of preparedness for teaching reading to adolescents with disabilities. Six models were fitted using multinomial logistic regression analyses. Results demonstrate the importance of two factors in preparing special educators who have a high sense of preparedness for teaching reading to adolescents with disabilities. The first is pre-service coursework that uses practice-based pedagogical approaches as opposed to passive lecture and the second is more extensive in-service professional development. The results are discussed in light of the Every Student Succeeds Act (ESSA) and its delegation of teacher preparation policy to state education agencies. Implications for future research and policy in special education teacher preparation are provided.